Morphological and Morphometric Analysis of Distal End of Ulna in Gujarat Region: A Cross-sectional Study - Shabina Dal; Kashyap Trivedi; Shailesh Patel (International Journal of Anatomy Radiology and Surgery)
Introduction: Distal end of the ulna is an important anatomical structure for normal hand functioning which is prone to damage such as fracture and avulsion of the ulnar styloid process, that causes distal radioulnar joint instability. Aim: To measure the morphometry and morphological variations of the distal end of ulna. Materials and Methods: A cross-sectional study was conducted in the Department of Anatomy, Government Medical College, Bhavnagar, Gujarat, India in August 2023. A total of 42 (21 on each side) distal end of dry human ulna of unknown gender, age and race were studied. Morphometric parameters include measurement of the Length of styloid process, Height of seat, width of pole and width of fovea with the help of digital vernier caliper. Morphological parameters include shape of styloid process and shape of pole. Descriptive statistics was used. Results: Mean length of styloid process on right and left side was 6±0.65 mm and 5.30±0.92 mm. Mean height of seat on right and left-side was 6.56±0.98 mm and 6.12±0.88 mm. Mean width of pole on right and left-side was 4.99±0.75 mm and 5.15±0.78 mm. Mean width of fovea on right and left-side was 2.58±0.42 mm and 2.68±0.46 mm, respectively. The majority shape of a pole was kidney (57.14%), followed by semicircular (19.04%), comma (16.66%) and semilunar (4.76%). Majority of styloid process was blunt (78.57%), followed by pointed (21.42%). Conclusion: The present study is useful for hand surgeons in dealing with distal ulnar injury and reconstruction of the distal radioulnar joint with prosthesis.